Science in the Supply Chain: Collaboration Opportunities for Advancing Sustainable Agriculture in the United States. Issue 1 (1st July 2017) - Thomson, Allison M.; Ramsey, Stewart; Barnes, Ed; Basso, Bruno; Eve, Marlen; Gennet, Sasha; Grassini, Patricio; Kliethermes, Brandon; Matlock, Marty; McClellen, Eileen; Spevak, Ed; Snyder, Clifford S.; et al.
Abstract : Core Ideas: Sustainability indicators for US agriculture demonstrate improvement since 1980. Emerging multi‐stakeholder initiatives are seeking to drive further improvement. Collaboration with the scientific community is key to achieving improvements. Consumers and corporations are increasingly interested in understanding the sustainability of agricultural supply chains and reducing the environmental impacts of food, fiber, feed, and fuel production. This emerging need to quantify environmental impacts from agricultural production creates an opportunity for collaboration with the scientific community. Without such collaboration, sustainability efforts risk failure by adopting unrealistic goals or misguided approaches. This commentary explores the role of science in Field to Market, a nonprofit organization developing a sustainability program for US commodity crops, and highlights opportunities to address emerging science challenges. We evaluate changes over the past 35 years in key environmental impacts of crop production used to inform land managers as well as companies that are committed to improvements. Achieving improvements will only be possible if three key gaps are addressed regarding available simulation models and data, scale of implementation and uncertainty, and effectiveness of conservation practices. Filling these gaps presents an opportunity for dialogue between scientists, farmers, and private‐sector stakeholders to advance scientific knowledge and promote the common objective of sustainable agriculture.